Heart rate variability, blood pressure variability, and baroreflex sensitivity in overtrained athletes - Baumert, M.; Brechtel, L.; Lock, J.; Hermsdorf, M.; Wolff, R.; Baier, V.; Voss, A. (Clinical Journal of Sport Medicine, 2006)
Objective: To assess the effects of abruptly intensified physical training on cardiovascular control. Design: Retrospective longitudinal study. Setting: Research laboratory. Participants: Ten healthy athletes (5 men and 5 women) from track and field as well as triathlon.